2021
DOI: 10.3389/fcell.2021.619538
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Loss of BAF (mSWI/SNF) Scaffolding Subunits Affects Specification and Proliferation of Oligodendrocyte Precursors in Developing Mouse Forebrain

Abstract: Oligodendrocytes are responsible for axon myelination in the brain and spinal cord. Generation of oligodendrocytes entails highly regulated multistage neurodevelopmental events, including proliferation, differentiation and maturation. The chromatin remodeling BAF (mSWI/SNF) complex is a notable regulator of neural development. In our previous studies, we determined the indispensability of the BAF complex scaffolding subunits BAF155 and BAF170 for neurogenesis, whereas their role in gliogenesis is unknown. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…OL lineage-specific deletion of BRG1, a BAF complex ATPase, inhibits OL differentiation and myelination to a greater or lesser extent (Yu et al, 2013; Bischof et al, 2015), possibly depending on the choice of CRE driver and hence the precise stage of OL lineage development at which deletion occurs (Matsumoto et al, 2016). Consistent with these studies, conditional knockout (cKO) of CHD8 (Zhao et al, 2018) or CHD7 (He et al, 2016; Marie et al, 2018), which act respectively upstream or downstream of BRG1, inhibit OP proliferation and survival – as does cKO of BAF complex scaffold proteins BAF155 and BAF170, potentially inactivating both BRG1- and BRM-containing complexes (Abbas et al, 2021). Other CRCs have been implicated in the control of OL lineage progression; for example, cKO of both HDAC1 and HDAC2, histone deacetylases associated with the NuRD complex (Ye et al, 2009), inhibits OL differentiation, while cKO of EP400, an ATPase of the INO80/ SWR family, inhibits OL survival and myelination (Elsesser et al, 2019).…”
Section: Introductionmentioning
confidence: 86%
“…OL lineage-specific deletion of BRG1, a BAF complex ATPase, inhibits OL differentiation and myelination to a greater or lesser extent (Yu et al, 2013; Bischof et al, 2015), possibly depending on the choice of CRE driver and hence the precise stage of OL lineage development at which deletion occurs (Matsumoto et al, 2016). Consistent with these studies, conditional knockout (cKO) of CHD8 (Zhao et al, 2018) or CHD7 (He et al, 2016; Marie et al, 2018), which act respectively upstream or downstream of BRG1, inhibit OP proliferation and survival – as does cKO of BAF complex scaffold proteins BAF155 and BAF170, potentially inactivating both BRG1- and BRM-containing complexes (Abbas et al, 2021). Other CRCs have been implicated in the control of OL lineage progression; for example, cKO of both HDAC1 and HDAC2, histone deacetylases associated with the NuRD complex (Ye et al, 2009), inhibits OL differentiation, while cKO of EP400, an ATPase of the INO80/ SWR family, inhibits OL survival and myelination (Elsesser et al, 2019).…”
Section: Introductionmentioning
confidence: 86%
“…By extension, because aRGCs also give rise to oligodendrocytes during mammalian neocortical development, it is logical that oligodendrogenesis may also be perturbed in the absence of normal cell delamination in the neurepithelium during the active phase of aRGC transformation or division to produce pre-oligodendrocyte precursor cells. Indeed, an account has been given where the abnormally developing cortex (due to BAF complex ablation) with loss of AJ complex and increased delamination of Pax6 or Sox2-expressing aRGCs ( Nguyen et al, 2018 ), may have caused notable decrease in the number of OLIG2/PDGFRα-expressing oligodendrocyte precursor cells–and hence oligodendrocytes–in the early postnatal cortex of such mutants ( Abbas et al, 2021 ). Moreover, it was observed that neural stem cells or aRGCs lacking anchorage and proper stemness in the VZ are forced to differentiate into oligodendrocytes at the expense of astrocytes ( Niola et al, 2012 ).…”
Section: Significance Of Cell Delamination During Cortical Developmentmentioning
confidence: 99%
“…In the same line of reasoning, the production of oligodendrocytes in the developing cortex can be affected when certain factors involved in delamination are ablated. It is expected that the disturbance of the oligodendrogenesis program in the developing mouse cortex due to loss of BAF155 and BAF170 ( Abbas et al, 2021 ), lack ( Niola et al, 2012 ) or overproduction ( Kiszka, 2019 ) of cortical astrocytes will increase susceptibility to neuronal degeneration known to call forth neurodegenerative disorders. This proposed pathologic outcome implicating abnormal delamination of aRGCs remains to be explored.…”
Section: Implicating Effects Of Defective Cell Attachment or Dysregul...mentioning
confidence: 99%
“…Many non-histone proteins, such as p53, DNA (cytosine-5)-methyltransferase 1 (DNMT1), SOX2, LIN28A, HIF1a, NFkB/RelA, ERa, GLI3, and E2F1, are mono-methylated on speci c lysine residues by SET7 (SET7/9, SET9, SETD7 or KMT7) 25,26,[28][29][30][31][32] , which was originally isolated as a histone methyltransferase that mono-methylates H3K4 33,34 . Accumulating evidence indicates that methylation of lysine residues by SET7 on a group of non-histone proteins, such as DNMT1, E2F1, SOX2, NFkB/RelA, FOXO3, and STAT3 [35][36][37][38][39][40] , triggers the proteolytic destruction of these modi ed proteins.…”
Section: Introductionmentioning
confidence: 99%